DEVELOPMENT OF CHEMISTRY MODULE OF ACID-BASE SOLUTION MATERIALS BASED ON PROBLEM-BASED LEARNING - Siregar, Tiurlina; Wulandary, Senny; Samosir, Hotlan; Kelmaskosu, Natalia Debora Silpa (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
Modules are very important developed in chemistry learning. Modules as teaching materials are very minimal so that they become obstacles in chemistry learning, especially acid-base solution materials. Therefore, this study aims to develop and validate the feasibility of chemical modules on acid-base solution materials through a problem-based learning approach, as well as to examine the responses of students and teachers to the developed products. The method in this study uses research and development (R&D) methods and ADDIE is a development model applied as a methodology. The sample in this study was 25 students. The sampling technique is saturated samples. The module is validated by the material and media validators then validated by the teacher and asked for feedback from students. The data was processed using SPPS acid-base solution as the subject of this study. The module was developed because it is very feasible to be applied in chemistry learning to acid-base solution materials, based on the results of data analysis. The material validator gave an average score of 92% (very decent), the media validator 95% (very decent), the teacher's response to 96% (very good) and the students' response to the developed module was 98% (very good) and the average was 94% (very decent).